Anaerobic sewage treatment : a practical guide for regions with a hot climate - Haandel, Adrianus C. Van; Lettinga, Gatze (London, United Kingdom : Wiley, 1994)
This text describes sewage treatment using the Upflow Anaerobic Sludge Blanket digester, a treatment process developed at Wageningen Agricultural University, The Netherlands. The study demonstrates specifically how the process can be used in hot climates.
Sewage treatment and sewage treatment systems; application of anaerobic digestion to sewage treatment; design criteria of UASB reactors for sewage treatment; performance of UASB reactors treating sewage; pH value and stability in an anaerobic digester; sludge treatment; post-treatment of UASB effluent.
Includes index.
Keywords: SEWAGE SLUDGE DIGESTION